Improving Students Speaking Skills by Recount Text - Juita Mariani Simamora; Ramauli Sinaga; Sri Ninta Tarigan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The aim of this study was to find out whether there was a students ability to speaking after learning recount text. This type of research is quantitative. The data used is the value of students in knowing improvenment in speaking students to understanding recount text. Data collection techniques in this study were interviews as introductory stage with students and teacher to find out the improvenment in students speaking skills, observation, questionnaire and data collection. The conclusion of this research is that after doing cycle 1 and cycle 2 the recount text can to improve students ability Key words: speaking skills, recount text.